The impact of therapeutic persuasiveness on engagement and outcomes in unguided interventions: A randomized pilot trial of a digital parent training program for child behavior problems - Amit Baumel; Or Brandes; Håvar Brendryen; Fred Muench; John M. Kane; Chen Saar (Internet Interventions, 2023)
Understanding how to design engaging unguided digital health interventions is key in our ability to utilize digital tools to improve access to care. Therapeutic persuasiveness (TP) is a design concept that relates to how the digital intervention features as a whole should be designed to encourage users to make positive changes in their lives, while reducing the experienced effort required from them to engage in these activities. In our previous work, we examined the user traffic of publicly available programs, finding programs' TP quality to be a reliable, robust, and stable predictor of real-world usage; however, these findings have not been subject to experimental manipulation in a controlled trial. The current study examined the impact of TP quality in digital parent training programs (DPTs) aimed at treating child's behavior problems. We conducted a pilot randomized controlled trial comparing two interventions that utilize the same evidence-based content of established DPTs, but that differ in terms of the quality of TP (standard: DPT-STD; enhanced: DPT-TP). Altogether, parents from 88 families who have a child with behavior problems were enrolled in the study. Compared to DPT-STD (n = 43), participants allocated to DPT-TP (n = 45) used the program significantly more (ps < 0.001; Cohen's ds = 0.91–2.22). In terms of program completion, 68.9 % of DPT-TP participants completed it compared to 27.9 % of DPT-STD participants. Significant differences between the interventions were also found in reported improvements in child behavior problems favoring DPT-TP (ps < 0.05; Cohen's ds = 0.43–0.54). The results point to the importance of adequate product design and the utilization of conceptual frameworks in order to improve user engagement challenges.